Case Reports-Conjunctivoblepharon; A Variant of Anklyloblephron - Ahmed, Munawar (Pakistan Journal of Ophthalmology, 2016)
We report a patient seen with an unusual condition affecting the eyelids and conjunctiva seen in 2015 at the department of ophthalmology Liaquat University of Medical and Health sciences Jamshoro. Affected patient was reviewed for his clinical history, examination findings, external photographs, and the result of treatment. This is a new ocular problem in which tarsal conjunctiva of upper and lower lid is fused and can be called Conjunctivoblepharon. Key words: Eye lids, conjunctiva, vision, primary position.